Clinico-laboratory Profile of Enteric Fever and Antibiotic Sensitivity Pattern in Hospitalized Children - Rahat, Farhana; Ghosh, NK; Iman, Kazi; Khanam, Morsheda; Sultana, Azmeri; Haque, Md Fazlul (Bangladesh Journal of Child Health, 2018)
Background: Enteric fever is endemic in Bangladesh. This is an important cause of morbidity and mortality in developing countries. The aim of the study was to evaluate the clinical and laboratory profiles, culture positivity rate and sensitivity pattern of Salmonella enterica. Methodology: This was an observational study carried out in a tertiary care hospital in Dhaka, Bangladesh during the period from January to December, 2017. Total 120 children who had enteric fever diagnosed either by positive blood culture or widal test with significant titre for Salmonella Typhi or Paratyphi were enrolled in the study. Results: Fever and abdominal pain were the main presenting symptoms. Leucocyte and platelet count were normal whereas ALT and CRP found to be elevated. Culture positivity rate in our study was 43.33%. Of the culture positive isolates, 88.46% were Salmonella Typhi and 11.53% were Salmonella Paratyphi. All the isolates were sensitive to third and fourth generation cephalosporins while 79.54% showed intermediate sensitivity to ciprofloxacin. Conclusion: A good sensitivity to third and fourth generation cephalosporins against Salmonella was noted whereas ciprofloxacin found to be less sensitive. Ceftriaxone showed remarkable efficacy when used as monotherapy. Bangladesh J Child Health 2018; VOL 42(2) :54-57